Pengaplikasian Diksi dan metode pembelajaran dalam Layanan Bimbingan Konseling Format Klasikal secara Daring - Cindy Marisa; Kasamanah Kasmanah; Arief Muda Kusuma (ABSYARA: Jurnal Pengabdian Pada Masayarakat, 2022)
Education is one field that needs to adapt carefully in providing the learning process in the conditions of the COVID-19 pandemic. Guidance and Counseling services are part of education which also faces challenges. The COVID-19  pandemic has created new problems for Guidance and Counseling Teachers in Bogor Regency. Therefore guidance and counseling services still need to be carried out effectively in the concept of distance learning using learning methods following the current pandemic conditions. In addition, diction in conveying information to students also needs to be a concern so that the service is felt to be effective and impacts positive and structured behavior change. Based on these needs, the community service team organizes activities to increase the insight and skills of BK teachers in online counseling services. The activity was carried out with the concept of a seminar taking into account health protocols, which was attended by 50 SMK BK teachers in Bogor Regency. The results of this activity indicate an increase in the understanding and skills of BK teachers in optimizing counseling services. BK teachers can vary the use of diction in communicating and use learning methods adapted to the class's characteristics so that learning is student-centered and more enjoyable within the framework of providing counseling services in a classical format